2023
DOI: 10.1039/d2ta09916k
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency enhancement of CZTSe solar cells based on in situ K-doped precursor

Abstract: An in-situ potassium (K)-doped copper–zinc–tin–sulfide (CZTS) precursor is prepared and annealed through selenization. After comprehensive optimization of the annealing, a cell with an efficiency of up to 12.62% is obtained,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…[34,60] The decrease in the density of Sn-related deep defect states may be due to the existence of element K in the absorber layer of the K 2 S device which enhances the element diffusion rate, allowing a larger fraction of the absorber to participate in the evaporation and inclusion during selenization, stabilizing the Sn content. [52] This demonstrates the necessity of selecting K 2 S material for CZTSSe, where the presence of K 2 S is able to passivate deep energy level defects, thus reducing the defect problems that may result from the increased S content. Further calculations of 𝜎×N T to evaluate the trap lifetime are shown in Figure 7j.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[34,60] The decrease in the density of Sn-related deep defect states may be due to the existence of element K in the absorber layer of the K 2 S device which enhances the element diffusion rate, allowing a larger fraction of the absorber to participate in the evaporation and inclusion during selenization, stabilizing the Sn content. [52] This demonstrates the necessity of selecting K 2 S material for CZTSSe, where the presence of K 2 S is able to passivate deep energy level defects, thus reducing the defect problems that may result from the increased S content. Further calculations of 𝜎×N T to evaluate the trap lifetime are shown in Figure 7j.…”
Section: Resultsmentioning
confidence: 99%
“…This PL shows that K 2 S can effectively passivate the acceptor defect (V Sn ), and it has been demonstrated that K is able to reduce Sn-related defects by promoting elemental diffusion to stabilize the Sn content. [52] Therefore, the supply of K 2 S modified the defect chemistry of CZTSSe by reducing the transition path passing through the defects and passivating the nonradiative defects in CZTSSe. In multi-crystalline CIGS and CZTSSe materials, potential fluctuation usually can act as traps for carriers to hinder carrier transport and diffusion.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The details of fabrication of CZTSSe layer can be found in other studies. [ 35,36 ] 600 nm‐thick ZnO:Al(AZO) film was prepared by sputtering ZnO:Al (Al 2 O 3 : 2 wt%k ZnO:Al(AZO) film was substrate temperature of 200 °C. CdS layer was obtained by chemical bath deposition which utilized cadmium surface as the source of Cd, thiourea as the source of S, and ammonia to adjust the pH value of the solution.…”
Section: Methodsmentioning
confidence: 99%
“…The substrate may have controlled movement for uniform film deposition (Figure 4). The deposition of CZT(S/Se) films by evaporation can be achieved through two different approaches: single-step deposition [30,31], where all the precursors are simultaneously deposited and then followed by sulfurization, and sequential two-step deposition using different metallic or binary precursors, in different combinations and sequences, such as Cu/Sn/Zn/Cu, Cu/Sn/Cu/Zn [32], Cu-ZnS-Sn [33] or CuSn/Zn/Se/CuSn/Se [34], followed by annealing with a sulfur or selenium source.…”
Section: Evaporationmentioning
confidence: 99%